Rangelands Atlas Testimonies - International Livestock Research Institute; International Union for Conservation of Nature; World Wide Fund for Nature; Food and Agriculture Organization of the United Nations; United Nations Environment Programme; International Land Coalition (International Livestock Research Institute, 2021)
This film provides a short introduction to the global Rangelands Atlas 2021 with testimonies from the international partners involved in its production. Produced by Marco Buemi and Patrick Augenstein